Sayonara Football : Game On - Book 1 1 - Arakawa, Naoshi; Corwin, Devon (New York : Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2020)
"High-octane girls soccer action mixes with the drama of high school in this cleats-out manga from the creator of Your Lie in April! game on. Midori and Sumire are soccer stars at rival middle schools, destined to collide : ones a striker, the others a goalie. But the two girls end up in the same high school, with a lazy coach and a bizarre teammate, Nozomi, who brags that shes a soccer prodigy but cant seem to stop kicking the ball into her own goal. To become champions, Midori and Sumire will have to get over their rivalry and work some magic on the field--not to mention the challenges of growing up."--
In English, translated from Japanese.
Keywords: Soccer; Comic books, strips, etc; Teenage girls; Comic books, strips, etc; High school students; Comic books, strips, etc; Soccer goalkeepers; Comic books, strips, etc; Women soccer players; Comic books, strips, etc; Teamwork (Sports); Comic books, strips, etc; Comic books, strips, etc; Graphic novels; Sports comics; Graphic novels; Comics (Graphic works); Fiction